Myasthenia gravis and chronic inflammatory demyelinating polyneuropathy in the same patient – a case report. (3rd June 2018) - Quan, Weiwei; Xia, Junhui; Tong, Qiuling; Lin, Jie; Zheng, Xiaolu; Yang, Xuezhi; Xie, Dewei; Weng, Yiyun; Zhang, Xu
ABSTRACT: Purpose: To investigate the clinical character, diagnosis and treatment of chronic inflammatory demyelinating polyneuropathy accompanying myasthenia gravis so as to improve the understanding of such diseases. Materials and methods: A case of chronic inflammatory demyelinating polyneuropathy combined with myasthenia gravis were analyzed retrospectively with review of the literature. Results: This man was presented with chronic progressive sensory symptoms, flaccid tetraparesis, areflexia and protein-cell dissociation of cerebrospinal fluid. Nerve conduction study was indicative of demyelinating neuropathy. He was suspected as chronic inflammatory demyelinating polyneuropathy and treated with high-dose glucocorticoids. However, his condition worsened. Four months later, he was admitted and was diagnosed as combination of chronic inflammatory demyelinating polyneuropathy and myasthenia gravis. Good clinical results were observed after he was treated with pyridostigmine bromide, prednisone and mycophenolate mofetil. Conclusions: This case warns clinicians to be aware of these two diseases presenting in the same patient, and the possible implications on treatment choices. A common immunological abnormality might exist in this rare association, but it still remains unknown.